Podobe živali v poeziji Daneta Zajca - Harlamov, Aljoša (Jezik in slovstvo, 2016)
Applying the theoretical framework of animal studies, animal depictions in the poetry of Dane Zajc can be divided into two groups. In the first are poems in which the (lyrical) subject maintains a hierarchical dualistic relationship towards the animal, which is a legacy of the modern rational subject; in the second are poems in which the (lyrical) subject exceeds the anthropocentric perspective and the hybridisation of the subject begins. The latter presupposes a permeability of human and animal categories, and with it the permeability of the subject, effectively resulting in its disintegration and a more consistent use of modernist poetic devices.
Keywords: Zajc, Dane; Slovene literature; slovenska književnost; slovenska poezija; slovenski pesniki; motiv živali; pesniški subjekt; modernizem; literarne študije